Sulfuric acid effect and application of freezing-thawing curing on long fiber reinforced metabentonite and slag-based geopolymer composites - Aygormez, Yurdakul (TECHNO-PRESS, 2021)
In this study, different types of metabentonite (MB) and slag (S)-based geopolymer were produced based on origin, polyvinyl alcohol (PVA) and basalt (B) fiber at different percentages of 0.2%, 0.4%, and 0.6%. A total of 7 series were produced. Two steps of curing method were applied for the samples, the first step was at room temperature from day 1-7, and the second step freezing-thawing from 8-28 days. Thus, the applicability of a curing method that used less energy instead of heat curing was investigated. Due to the freezing-thawing curing, the continuation of geopolymerization reactions was ensured and a compact structure was created. The produced samples were subjected to 10% sulfuric acid effect for 3 months after the 28th day. Compressive strength, flexural strength, ultrasonic pulse velocity (UPV), and weight losses due to acid effects were found. Despite the decrease in mechanical properties after the acid effect, the geopolymer products didn't experience easy dispersal because they had strong aluminosilicate bonds, crystalline phase formation, morphology, and lower calcium content that provided high stability. Also, SEM, XRD, FT-IR, and TGA-DTA analyzes and visual inspection resulting from the acid effect were examined.
Keywords: basalt fiber; freezing-thawing; geopolymer; metabentonite; PVA fiber; slag; sulfuric acid; FLY-ASH; MECHANICAL-PROPERTIES; SODIUM-SILICATE; METAKAOLIN; CONCRETE; RESISTANCE; CEMENT; MORTAR; PERFORMANCE; DURABILITY; Construction & Building Technology; Engineering; Materials Science